2013
DOI: 10.1063/1.4826594
|View full text |Cite
|
Sign up to set email alerts
|

New insights into designing metallacarborane based room temperature hydrogen storage media

Abstract: Metallacarboranes are promising towards realizing room temperature hydrogen storage media because of the presence of both transition metal and carbon atoms. In metallacarborane clusters, the transition metal adsorbs hydrogen molecules and carbon can link these clusters to form metal organic framework, which can serve as a complete storage medium. Using first principles density functional calculations, we chalk out the underlying principles of designing an efficient metallacarborane based hydrogen storage media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…However, this may lead the production of highly diluted H 2 , which may in turn reduce the potential for commercial applications. Utilization of bioreactors covered with materials, such as metallacarboranes, with high reversible capacity for binding H 2 at low temperatures [ 30 ] might be a way to avoid H 2 uptake.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may lead the production of highly diluted H 2 , which may in turn reduce the potential for commercial applications. Utilization of bioreactors covered with materials, such as metallacarboranes, with high reversible capacity for binding H 2 at low temperatures [ 30 ] might be a way to avoid H 2 uptake.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical study restricted to metallacarboranes, which included 7-vertex M(C 2 B 4 H 6 ) and 14-vertex M 2 (C 4 B 8 H 12 ) as well as 12-vertex M(C 2 B 9 H 11 ) and M 2 (C 2 B 8 H 11 ) systems, found that metallacarborane-based MOFs are excellent candidates for hydrogen storage, with a capacity of up to five H 2 molecules per transition metal atom; scandium and titanium are predicted to have the highest capacity (∼8 wt%). 137 Other theoretical investigations, on titanium sandwiches with planar C 3 B 2 H 5 rings, 138 Li and Na complexes with planar C 4 B 2 H 6 rings, 139 and scandium-carborane complexes, 140 "paddlewheel" nodes, three architecturally distinct MOFs were obtained, one of which is depicted in Fig. 25.…”
Section: Carboranes In Metal-organic Frameworkmentioning
confidence: 95%
“…1(b). The inclusion of boron in the Ti cluster enhances the charge depletion near the Ti atoms, rendering more d-orbitals available for H 2 adsorption [49]. This charge depletion is most in the case of Ti 2 B and continues to reduce systematically in the next four clusters (Ti 3 B > Ti 4 B > Ti 5 B > Ti 6 B).…”
Section: Resultsmentioning
confidence: 90%